Housing Finance and Mortgage-Backed Securities in Mexico - Zanforlin, Luisa (IMF Working Papers; Working Paper ;, 2008)
This paper reviews the Mexican experience with the securitization of residential mortgages. It highlights the key legislative and institutional reforms leading to the development of primary and secondary mortgage markets and reports the main features and valuation practices of the RMBS markets. The paper identifies areas warranting close attention to improve the outlook for the Mexican RMBS market and draws some lessons from the recent U.S. subprime mortgage market problems.